Implementation Of 'Usyur in Tax Revenue During the Covid-19 Period in Medan City - Nurlaily Nurlaily; Muhammad Yafiz; Yenni Samri Juliati Nasution (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
The coronavirus has had a tremendous impact on the world economy, many people's businesses have experienced a decline in revenue during covid-19. Hotel and restaurant tax revenues during the covid-19 period have also been paralyzed. So that tax deposits become the heaviest burden for business actors. In this case, how does the concept of 'Usyur see the problems that plague this world so that tax revenues during the Covid-19 pandemic. This research uses qualitative research methods with descriptive analysis. A qualitative approach is an approach that seeks to interpret the meaning of an event as an interaction of human behavior in a particular situation. The results found are that 'Usyur provides relief to business actors when an outbreak hits the world, but in its implementation it often experiences obstacles and obstacles and its application has not been implemented in Indonesia. 'usyur has not been fully implemented even though there are sharia hotels and restaurants, 'usyur has not been as busy as it is going well, although the concept will lead to the concept of sharia tax revenue. This is an input for future business actors in realizing sharia tourism and hotels. Virus corona telah membawa dampak yang sangat luar biasa terhdapa perekonomian dunia, banyak usaha masyarakat yang mengalami penurunan penerimaan selama covid-19. Penerimaan pajak hotel dan restoran dimasa covid-19 juga mengalami kelumpuhan. Sehingga penyetoran pajak menjadi beban terberat bagi pelaku usaha. Dalam hal ini bagaimana konsep ‘Usyur melihat permasalahan yang melanda dunia ini sehingga dalam penerimaan pajak ketika masa pandemi covid-19. Penelitian ini menggunakan metode penelitian kualitatif dengan analisis deskriptif. Pendekatan kualitatif adalah pendekatan yang berusaha menafsirkan makna suatu peristiwa sebagai interaksi perilaku manusia dalam situasi tertentu. Adapun hasil yang ditemukan adalah bahwa ‘Usyur memberikan keringanan kepada para pelaku usaha ketika sebuah wabah melanda dunia, namun dalam implementasinya sering mengalami hambatan dan kendala serta penerapannya belum begitu diterapkan di Indonesia. ‘usyur belum sepenuhnya diterapkan meskipun ada hotel dan restoran syariah, ‘usyur belum sepeuhnya berjalan dengan baik, meskipun pada konsep akan mengarah kepada konsep penerimaan pajak secara syariah. Hal ini menjadi masukkan untuk pelaku usaha kedepannya dalam mewujudkan wisata dan hotel syariah.